Ecological Feminism Issues Depicted in Moana's Screenplay by Jared Bush - Susi Ambarwa; Radius Setiyawan; Pramudana Ihsan (Tell : Teaching of English Language and Literature Journal, 2018)
The purpose of this research is to reveal whether Moana’s Screenplay by Jared Bush can be considered as an eco-feminism reading or not. To prove this hypothesis, the researcher analyzes Moana’s Screenplay through find out the characteristics of the main character that reflect ecological feminism and reveals the relationship between man, woman, and nature in Moana’s screenplay using eco-feminism perspective. The researcher uses descriptive qualitative methods in analyzing the data. The researcher found that eco-feminism issues were clearly shown in this screenplay. First, the main character in Moana’s Screenplay was not described as a weak woman but she showed the characteristics of leadership, ambitious, and courageous where these characters usually owned by man. She was described as a woman who loved their people and the environment which is a reflection of ecological feminism. Second, the relationship between man and woman was illustrated that male characters dominated woman both verbally and mentally. Third, regarding the relationship between man and nature, it was found that nature was dominated because man saw nature as a resource to meet human needs. Finally, related to the relationship between woman and nature, it was revealed that woman was closer to nature than man so they can live in harmony.